The Emergence of Age-Friendly Communities: Highlighting the Town of Bucksport - Bradney, James (Maine Policy Review, 2015)
James Bradney highlights the activities and services available in Bucksport, Maine, that are enabling the town to meet the needs of its older adult population. The town is one that is participating in the Thriving in Place Initiative of the Maine Health Access Foundation.
Keywords: age-friendly communities; Maine; aging; Bucksport; Thriving in Place